BiVO4 Fern Architectures: A Competitive Anode for Lithium‐Ion Batteries. Issue 21 (19th October 2017) - Dubal, Deepak P.; Patil, Deepak R.; Patil, Santosh S.; Munirathnam, N. R.; Gomez‐Romero, Pedro
Abstract: The development of high‐performance anode materials for lithium‐ion batteries (LIBs) is currently subject to much interest. In this study, BiVO4 fern architectures are introduced as a new anode material for LIBs. The BiVO4 fern shows an excellent reversible capacity of 769 mAh g −1 (ultrahigh volumetric capacity of 3984 mAh cm −3 ) at 0.12 A g −1 with large capacity retention. A LIB full cell is then assembled with a BiVO4 fern anode and LiFePO4 (LFP, commercial) as cathode material. The device can achieve a capacity of 140 mAh g −1 at 1C rate, that is, 81 % of the capacity of the cathode and maintained to 104 mAh g −1 at a high rate of 8C, which makes BiVO4 a promising candidate as a high‐energy anode material for LIBs. Abstract : Batteries just wanna have fern : BiVO4 fern architectures are introduced as a new anode material for lithium‐ion batteries (LIBs). The BiVO4 fern shows an excellent reversible capacity and large capacity retention. A LIB full cell is then assembled with a BiVO4 fern anode and LiFePO4 as cathode material. The device can achieve a capacity of 140 mAh g −1 at 1C rate, which makes BiVO4 a promising a high‐energy anode material for LIBs.